Effectiveness of Hydrotherapy with Mirror Theraphy to Increase Muscle Strength of Ishemic Stroke Patients - Baharudin, Virginia Eka Putri A.; Nurhalisah; Addini, Ragil Aidil Fitriasari (Physiotherapy and Physical Rehabilitation Journal, 2022)
Stroke is a central nervous breakdown disease that causes due to loss and dysfunction of brain parts Disability in the blood supply to the brain blood vessels. Among these three classifications, ischemic stroke is among the most common types of stroke, which is about 70 % of the whole case. As a top-down rehabilitation hegemon, mirror therapy improves lower limb motor function, balance, transferability and activities of daily living for stroke patients by increasing functional connectivity and activity in areas of the brain that promote motor function. It is indicated that hydrotherapy soaks warm feet with mirror therapy in the intervention group and mirror therapy in the control group are equally effective in improving the muscle strength of the upper and lower extremities. Methodological quality of studies using the scholar, pubmed.